2001
DOI: 10.1128/jcm.39.1.357-361.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of PCR in Diagnosis and Prognosis of Visceral Leishmaniasis in Patients Coinfected with Human Immunodeficiency Virus Type 1

Abstract: A group of 76 consecutive human immunodeficiency virus (HIV)-positive patients with fever of unknown origin (n ‫؍‬ 52) or fever associated with pulmonary diseases was evaluated in order to assess the usefulness of PCR with peripheral blood in the diagnosis and follow-up of visceral leishmaniasis. We identified 10 cases of visceral leishmaniasis among the 52 patients with fever of unknown origin. At the time of diagnosis, all were parasitemic by PCR with peripheral blood. During follow-up, a progressive decline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
1
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 19 publications
1
54
1
2
Order By: Relevance
“…[21][22][23] These assays gave negative results after treatment and were unable to analyze the decrease in parasitic load during treatment. In typical cases of VL, the quantitative PCR showed that parasitemia decreases to undetectable levels between the third and the fourth administration of liposomal amphotericin B independently of the initial parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23] These assays gave negative results after treatment and were unable to analyze the decrease in parasitic load during treatment. In typical cases of VL, the quantitative PCR showed that parasitemia decreases to undetectable levels between the third and the fourth administration of liposomal amphotericin B independently of the initial parasitemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although different molecular methods have successively been evaluated for leishmaniasis diagnosis, PCR-based assays are the main molecular diagnostic tools, especially in immunosupressed patients [91][92][93][94].…”
Section: Molecular Methods: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…PCR protocols to detect Leishmania DNA in VL diagnosis have used a variety of samples, including spleen, lymph node, and bone marrow aspirates, whole blood, and buffy coat [92,[95][96][97][98][99][100][101].…”
Section: Molecular Methods: Polymerase Chain Reaction (Pcr)mentioning
confidence: 99%
“…This result differs from some previous publications, where much less time was required to achieve a negative PCR: from 17.5 days (8 days to 21 weeks) in the article by Antinori and others 24 to 3 months (2 weeks to 7 months) in the work by Lachaud and others 19 to 6 months according to Bourgeois and others 25 to between 6 and 21 weeks in the work by Pizzuto and others. 11 The reason justifying this difference is precisely the type of PCR used. In our case, the kinetoplast DNA was used as a target of amplification, which has a much lower detection threshold than small subunit ribosal RNA (SSU-rRNA).…”
Section: Discussionmentioning
confidence: 99%
“…Data exist regarding its use in peripheral blood and bone marrow samples, with sensitivities ranging from 73% to 100% and specificity close to 100% for the diagnosis of the initial VL episode, mainly in HIV-infected patients. [7][8][9][10][11][12][13][14][15][16][17][18] However, its value as a useful tool for monitoring VL in HIVinfected patients remains to be proven. Various published studies seem to correlate the presence of a high parasite load level in peripheral blood measured by PCR after an initial episode treated and cured with a higher risk of future clinical relapse (Table 1).…”
Section: Introductionmentioning
confidence: 99%